Assessment of State Capacity to Manage Forest and Land Fires in Kubu Raya Regency, West Kalimantan Province - Lestari Agustrihardaning (Graduate Program, 2014)
Forest and land fires in Kubu Raya Regency are caused by human activity such as farming by burning landand have caused a lot of environmental damage and material loss. There is a need to overcome or to minimize disaster by conducting activities aiming to reduce the risk and the impact. This paper focuses on the government capacity to address disaster, particularly forest and land fires in Kubu Raya Regency and describes government capacity, particularly within organizations, coordination among organizations, human and material resources, and budgets related to forest and land fires, in order to discover whether the capacity is strong or weak. It attempts to describe state capacity and to answer the question about the government capacity to manage forest and land fires in Kubu Raya Regency. The method that is used to analyze the question is a qualitative and descriptive method by doing interview and reviewing literature and documents related with the forest and land fires issues.This research found that government has the capability to address forest and land fires, but there does not exist a particular organization to handle the fires, lack of coordination, budget, and both human and material resources which proves that state capacity is still weak. Keywords: disaster, forest and land, state capacity